Orchidaceae nativas da região central de São Paulo, Brasil: florística, interação com forófitos, proposta de novas espécies e propagação in vitro de uma espécie ameaçada de extinção - Ferreira, Alessandro Wagner Coelho (2009)
Aiming to know the sorts of Orchidaceae of the central region of the State of São Paulo, from 1996 and more intensively from 2005, visits were carried out in 125 forest fragments of 23 local municípios, with weekly periodicity and also, fortnightly. The collect were assistematics, being each fragment visited in the biggest number of points. The species not identified in field, had collected examples (with authorization of the IBAMA and Forest Institute of São Paulo) and cultivated at green house up to the blooming. At least the floral parts were herborized and deposited principally in the Herbarium of the Federal University of São Carlos. 219 species were registered in 98 genera: 64 % epiphytic (140 species), 35% terrestrian (77) and 1% halfepiphytes (two). 15,5% from epiphytic (32) are also rock plants and 0,4% from terrestrian (one) is micoheterotrofic. The species with bigger richness were: Acianthera (13 species), Habenaria (12 species), Epidendrum (11 species), Bulbophyllum e Campylocentrum (10 species each), Pelexia (seven species), Cyclopogon (six species) and Baptistonia, Cattleya, Cyrtopodium and Encyclia (five species each). Four species (Anathallis sp., Baskervilla sp., Pelexia sp., Triphora sp.) they are in study and can be new táxons. Triphora sp. is a species of new incident for São Paulo and Baskervilla sp. can be the second valid species in Brazil for the genera. Probably that elevated number of species found is due to the fact that the studied area represents a region with influence of savana and Atlantic forest. From the total species studied 44,7 % are considered practically extinct in the nature, 42 % is threatened of extinction and 13,2 % is common. This fact is due not only to the deforestation and to the forest fragmentation, but also to his great collect. Regarding the species epiphytes, studies were done on interaction between these and his host tree (hostness), with approach on ecological nets, nestled structures and the factors wrapped in these relations, being taken into account and, also, if the time of interaction between them, analyzed through the phylogeny of the orchids and host tree, contributed to such a interaction. The structure interconnected of the web of interactions between species can be described through a net (graphs), i.e. a set of points (apexes, knots) that can or not be connected through lines (edges, connections). In a net between organisms, the knots represent the species of a locality and, the lines, interactions between the species. The study of the structure of the nets, mutualistics or not, is still essentially in a descriptive phase. Pollination, dispersal of seeds and epiphytism, they have been studied and fitted in the category of non-trophic mutualistics relations in nets. The studies on interactions between communities can be usefull for the understanding which factors are wrapped in the origin and evolutive maintenance of them. This standard of interaction has been called nestled. A matrix was mounted describing the interactions between the species of orchids in the lines and the species of host tree in the columns. When there was interaction, the element aij of this matrix was considered 1 (one), when there was not this interation was considered 0 (zero). Through the NESTED program 3.0, was analyzed if the 139 species of epiphytic orchids were in structure nestled with 158 species of host tree, and also there was done the calculation of the rate NODF (Nestedness metric based on Overlap and Decerasing Fill). They were considered in the analyses, around 7.500 incidents of epiphytic orchids and 2.900 of host tree. For the phylogenetic analyses there was used the module PHYDIST of the program Phylocon 3.41. The drawings of the phylogenetic trees were done with help of IT ADDS-4 (Analyses des Données Ecologiques). The species of orchids that more interacted with the host tree were Polystachya spp., Rodriguesia decora (Lem.) Rchb. f. and Ionopsis utricularioides (Sw.) Lindl. The species of host tree that more they interacted with the orchids were: Calophyllum brasiliense Cambess., Talauma ovata A. St.-Hill. and Inga edulis Mart. The analyses were done with ANINHADO 3.0 (with two model null tests to 5 %), they showed that the standard of interaction between the orchids and the host tree is nestled and that this nestedness is not casual (NODF = 0.30, P <0.001 for two null models). With Phylocon tests, there was discarded the hypothesis of which the time of evolutive interaction between the orchids and his host trees has contributed to this nestled standard of interaction. Probably, this nestled standard was developed due to attributes of the host tree, such as roughness of the bark, released substances exudated from cuticle and hidatodes, degree of inclination of the stem and branches, age dynamic of the top and moisture of the environment in which the host tree is (the most wet environments favor the establishment of a bigger number of species of orchids). Also, it was suggested what micorrizes already existent to the trees could contribute for the nestled interaction, as soon as the seeds of orchids only germinate in the nature, if associated to these fungus. It seems that the accumulation of organic matter in the surface of the host tree favors the appearance of the micorrizes (the majority is saprophytic), that for his time, favor the appearance of the orchids. For last, the propagation was carried out in vitro, of Baptistonia pubes (Lindl.) Chiron & V.P. Castro, a threatened species of extinction in the state of São Paulo. Such a propagation was for method assymbiotic. They were tested if the pH and the constitution of the medium of culture were influencing the germination, growth and of B. pubes development. The inoculation of the tiny seeds of this orchid was made using a micropipette. Were weighed 0,0001 of seeds grams of this orchid and diluted in 3,5 mL of water with Tween detergent. Prior countings appreciated the average of seeds found in each micropipetation (around 98). Besides the use of the culture media Murashig-Skoog (MS), another culture media was used dwarf banana added with NPK 20-20-20 Plant Prood (BAN). For germination and growth, the tested pHs were 5,2 and 6,2 (based on data available in the literature). However in the germination, the culture media MS had the concentration of the macronutrients half reduced. In the plantules obtained for chiming, the pH of germination it was of 5,2 (so much in the media MS/2 as in the environment BAN). The plantules were sowed and rung in laminating flow and cultivated in environment controlled for around eight months. They were analyzed after this period, the fresh mass, the length of the biggest root, the biggest length of the air part and the number of roots. The statistical analyses were based on the test of Tukey (5%). The seeds germinated on average 15 days after the inoculation, in all the conditions. The percentage of germination varied between 2,6 to 11,6 %, and the biggest percentage took place in pH=5,2 BAN and the shortest in pH=6,2 MS/2. The way BAN was more efficient in the germination. The pHs, in each environment, altered significantly the averages of the germinated seeds. The growth of the plantules showed better results in the nourishing medium with dwarf banana (pH=5,2), probably due to the complexity nutritional of this of culture media.